2003
DOI: 10.1063/1.1620676
|View full text |Cite
|
Sign up to set email alerts
|

Organic light-emitting diodes driven by pentacene-based thin-film transistors

Abstract: Articles you may be interested inFlexible full color organic light-emitting diode display on polyimide plastic substrate driven by amorphous indium gallium zinc oxide thin-film transistors Appl. Phys. Lett. 95, 013503 (2009);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 19 publications
2
70
0
2
Order By: Relevance
“…3(b) for selected intramolecular phonons. Note that the intermolecular phonons have either zero or very small minimum frequency since they correspond to transverse acoustic (TA) and longitudinal acoustic (LA) vibrations (modes 1-3) or other rigid vibrations or librations of the molecules (modes [4][5][6][7][8][9][10][11][12]. By contrast, the intramolecular modes 20-90 in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(b) for selected intramolecular phonons. Note that the intermolecular phonons have either zero or very small minimum frequency since they correspond to transverse acoustic (TA) and longitudinal acoustic (LA) vibrations (modes 1-3) or other rigid vibrations or librations of the molecules (modes [4][5][6][7][8][9][10][11][12]. By contrast, the intramolecular modes 20-90 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Organic semiconductors are lead candidates for novel optoelectronics and spintronics applications [1,2]. Crystals like pentacene and rubrene are already widely used in organic field-effect transistors and light-emitting devices [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Anthracene (C 14 H 10 ) and pentacene (C 22 H 14 ) adsorbed on the Ag(111) surface are particularly interesting systems because of the frequent use of silver as electrode and the promising properties of the anthracene and pentacene compounds; both compounds exhibit high carrier mobility 1 and excellent electroluminescence and photoluminescence 2 , and have great potential for use in organic light-emitting diodes 3 and organic field effect transistors 4 . Experimental studies have reported that both anthracene and pentacene monolayers weakly adsorb on Ag(111), as characteristic of physisorption or weak chemisorption [5][6][7][8][9][10] , which suggests that van der Waals interactions (vdW) play an important role in the binding of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…而对于任何可能的实际应用, 一般要求场效应晶体管的迁移率超过 0.01 cm 2 •V -1 •s -1 , 开关比大于 10 3 [5] . 有机半导体材料是 OFET 中的核心 部件, 其性能直接决定晶体管的优劣 [6] .…”
Section: 引言unclassified